2017
DOI: 10.1186/s40562-017-0091-6
|View full text |Cite
|
Sign up to set email alerts
|

Soil erosion modeled with USLE, GIS, and remote sensing: a case study of Ikkour watershed in Middle Atlas (Morocco)

Abstract: The Ikkour watershed located in the Middle Atlas Mountain (Morocco) has been a subject of serious soil erosion problems. This study aimed to assess the soil erosion susceptibility in this mountainous watershed using Universal Soil Loss Equation (USLE) and spectral indices integrated with Geographic Information System (GIS) environment. The USLE model required the integration of thematic factors' maps which are rainfall aggressiveness, length and steepness of the slope, vegetation cover, soil erodibility, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 34 publications
2
43
0
11
Order By: Relevance
“…The results of the combination of effective factors in erosion showed that soil erosion is most associated with the C factor, followed by LS and R factors, which is in accordance with the results of El Jazouli et al [73]. This means that land uses with low and poor density of vegetation cover have the maximum amount of C factor and the greater risk of erosion.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the combination of effective factors in erosion showed that soil erosion is most associated with the C factor, followed by LS and R factors, which is in accordance with the results of El Jazouli et al [73]. This means that land uses with low and poor density of vegetation cover have the maximum amount of C factor and the greater risk of erosion.…”
Section: Discussionsupporting
confidence: 88%
“…Ashiagbor et al [36] likewise modelled the spatial distribution of soil erosion in the Densu River Basin of Ghana using RUSLE and GIS tools, and used the model to explore the connection between the catchment's soil erosion and the contributory factors. El Jazouli et al [19] evaluated soil erosion susceptibility in the Middle Atlas Mountain-Morocco using the USLE and the spectral index approach and realized an agreement between the two. Kayet et al [37] used the RUSLE and Soil Conservation Service (SCS) curve number (CN) to estimate soil loss in the Kiruburu and Meghahatuburuu mining sites.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, effective catchment management is needed to ensure the sustainability of natural resources both for the current and future generation [17,18]. This will require timely information on the rate and amount of soil loss and delineation of degraded areas [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A erosão do solo é um processo que ocorre naturalmente e é um fenômeno geológico normal, associado ao ciclo hidrológico. Ademais, pode ser considerado também, como um processo gradual que ocorre quando o impacto da água separa e remove partículas do solo causando a deterioração do solo (FARIA et al, 2003;SILVA et al, 2013;CORRÊA et al, 2015;EL JAZOULI et al, 2017).…”
Section: Introductionunclassified